The Effect of Regional Government's Finance Ratio to Human Development Index of Provincial Government in Indonesia - Ramadhan, Arie Vicky Galan; Setiawati, Erma (Prosiding University Research Colloquium, 2022)
The abstract must be short, interesting, simple, and easy to understand without reading the entire article. Therefore, avoid jargon, abbreviations and references. In writing abstracts, the author must be accurate, use the right words, and convey the meaning of the study. A good abstract contains the problem statement and purpose, how the research is carried out (the method), the results, and concludes with a brief statement of conclusions. In the abstract keywords are also always included. Keywords are used to index an article and are the label of an article. [Century 10 pt, italic] The aim of this research is to examine the effect of Regional Government’s Finance Ratio based on the Regional Government’s Finance Report to Human Development Index that used as a measure to evaluate the regional government’s performance on the public service. The Regional Government’s Finance Ratio which used in this research is Ratio of Decentralization’s Level, Ratio of Regional’s Finance Dependency, Ratio of Regional’s Finance Autonomy, Ratio of Regional’s Real Income Effectiveness, and Ratio of Regional’s Tax Effectiveness. The researcher gets the sample by using purposive sampling to all of the provinces in Indonesia on 2016-2018. The analyzing data uses multiple linear regression analysis method by using SPSS Software and Microsoft Office Excel. The result of this research shows that Ratio of Decentralization’s level has effect to Human Development Index, meanwhile Ratio of Regional’s Finance Dependency, Ratio of Regional’s Finance Autonomy, Ratio of Regional’s Real Income Effectiveness, and Ratio of Regional’s Tax Effectiveness have no effect to Human Development Index.